Articular degeneration after subchondral cementation for giant cell tumors at the knee. (September 2022) - Wechsler, C.; Hodel, S.; Stern, C.; Laux, C.J.; Rosskopf, A.B.; Müller, D.A.
Abstract: Purpose: To quantify joint degeneration and the clinical outcome after curettage and cementation in subchondral giant cell tumors of the bone (GCTB) at the knee. Methods: We conducted a retrospective analysis of 14 consecutive patients (seven female, seven male) with a mean age of 34 years (range 19–51) who underwent curettage and subchondral cementation for a biopsy-confirmed GCTB at the distal femur or the proximal tibia between August 2001 and August 2017, with a mean follow-up period of 54.6 months (range 16.1–156 months). The Whole-Organ Magnetic Resonance Imaging Score (WORMS), Kellgren-Lawrence (KL) classification, and Musculo-Skeletal Tumor Society (MSTS) score were assessed. Results: Radiological degeneration progressed from preoperative to the latest follow-up, with a median WORMS from 2.0 to 4.0 (p = 0.006); meanwhile, the median KL score remained at 0 (p = 0.102). Progressive degeneration (WORMS) tended to be associated with the proximity of the tumor to the articular cartilage (mean 1.57 mm; range 0–12 mm) (p = 0.085). The most common degenerative findings were cartilage lesions (n = 11), synovitis (n = 5), and osteophytes (n = 4). Mean MSTS score increased from 23.1 (preoperatively) to 28.3 at the latest follow-up (p < 0.01). Seven patients (50%) were treated for a local recurrence, with six revision surgeries performed. Removal of the cement spacer and filling of the cavity with a cancellous autograft was performed in seven patients. Conversion to a total knee arthroplasty was performed in one patient for local tumor control. Conclusions: Cementation following the curettage of GCTB around the knee is associated with slight degeneration at medium-term follow-up and leads to a significant reduction in pain. Removal of the cement and reconstruction with an autograft may be beneficial in the long term. Highlights: Subchondral cementation after curettage of giant cell tumors at the knee is associated with slight articular degeneration. Subchondral cementation after curettage leads to a significant reduction of pain. The role of bone cement (PMMA) in terms of articular degeneration remains unclear.